2012
DOI: 10.1002/car.1205
|View full text |Cite
|
Sign up to set email alerts
|

In Demand: Therapeutic Services for Children and Young People Who Have Experienced Sexual Abuse

Abstract: This paper describes the key findings of an NSPCC study estimating need, in the UK, for therapeutic services for children who have experienced sexual abuse. This is based upon current estimates of the prevalence and impact of sexual abuse towards children and young people against the availability of therapeutic services in the UK. Data were collected on service location, availability, scope and coverage across England, Wales, Northern Ireland and Scotland. Researchers: (1) mapped 508 services; (2) collected da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Trauma exposure can cause neurobiological, emotional, social, and cognitive impairment in young children that can derail development (Chu & Lieberman, 2010). Despite the high trauma exposure (Finkelhor et al, 2005; Finkelhor et al, 2009), accessible treatment by trained therapists to deliver EBP to children exposed to trauma remains limited (Allnock et al, 2012). Stepped Care TF-CBT may serve as a model for developing and testing stepped care approaches to treating other types of childhood psychiatric disorders.…”
Section: Resultsmentioning
confidence: 99%
“…Trauma exposure can cause neurobiological, emotional, social, and cognitive impairment in young children that can derail development (Chu & Lieberman, 2010). Despite the high trauma exposure (Finkelhor et al, 2005; Finkelhor et al, 2009), accessible treatment by trained therapists to deliver EBP to children exposed to trauma remains limited (Allnock et al, 2012). Stepped Care TF-CBT may serve as a model for developing and testing stepped care approaches to treating other types of childhood psychiatric disorders.…”
Section: Resultsmentioning
confidence: 99%
“…Social workers were concerned with the sustainability of the service, not necessarily the quality of provision. Lengthy waiting times and the limited availability of appropriate services, particularly for teenagers, young people from minority ethnic groups and children with disabilities, was a disturbing reality; findings also observed by Allnock et al (2012).…”
Section: ) Main Findings: Practice Issues Knowledge and Confidencementioning
confidence: 98%
“…Research by Baginsky (2001) on support services for 12 to 16 year olds who had been sexually abused found 'patchy' provision in the UK, with particular service gaps for children from ethnic minority groups, children with disabilities and young people who displayed sexually harmful behavior. A more comprehensive study conducted across England, Wales, Northern Ireland and Scotland revealed a significant gap in the availability, accessibility and provision of therapeutic services for children who have experienced sexual abuse (Allnock et. al, 2012).…”
Section: Institutional Support and Service Provision For Csamentioning
confidence: 99%
“…These results resonate with previous studies which highlight that therapeutic services often have short-term, unstable and insecure funding arrangement that often interfere with CSA service provision. Organizations often search for new sources of funding and tend to spend large amounts of their time to renew and renegotiate existing funding, which in turn interferes with the actual day-to-day delivery of services to children and young people (Allnock et al, 2012).…”
Section: Capacity and Scales Of Operationmentioning
confidence: 99%